Original Intents: Individual Requirements for Candidates of Regional Representative Council - Ganiviantara Pratama (Fakultas Hukum Universitas Lampung, 2020)
The main problem of this research is that there is no firmness regarding the diction of individual words in the Constitution which is useful as a condition for nominating Regional Representative Council or Dewan Perwakilan Daerah (DPD) membership. This indecisiveness has led to the composition of DPD membership being dominated by members of political parties. This journal aims to explore the meaning of the diction of words contained in the 1945 NRI Constitution, namely